Television series of the 1990s : essential facts and quirky details - Terrace, Vincent, 1948- (Rowman & Littlefield, 2018)
"This book profiles characters who were featured in some of the most popular television shows of the 1990s. Each entry includes personal details that were revealed during each show's run: names, addresses, maiden names, nicknames, date of births, phone numbers, relatives, and other fascinating details"--